James P. Cannon and the origins of the American revolutionary left, 1890-1928 - Palmer, Bryan D. (Working class in American history., 2007)
Bryan D. Palmer's award-winning study of James P. Cannon's early years (1890-1928) details how the life of a Wobbly hobo agitator gave way to leadership in the emerging communist underground of the 1919 era. Written with panache, Palmer's richly detailed book situates American communism's formative decade of the 1920s in the dynamics of a specific political and economic context.